2010
DOI: 10.1186/1743-7075-7-66
|View full text |Cite
|
Sign up to set email alerts
|

Lotus leaf extract and L-carnitine influence different processes during the adipocyte life cycle

Abstract: BackgroundThe cellular and molecular mechanisms of adipose tissue biology have been studied extensively over the last two decades. Adipose tissue growth involves both an increase in fat cell size and the formation of mature adipocytes from precursor cells. To investigate how natural substances influence these two processes, we examined the effects of lotus leaf extract (Nelumbo nucifera-extract solution obtained from Silab, France) and L-carnitine on human preadipocytes and adipocytes.MethodsFor our in vitro s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Furthermore, in mature adipocytes, L-carnitine induced the expression of genes involved in β-oxidation and lipolysis and suppression of genes involved in adipogenesis [19]. Finally, the direct effect of L-carnitine on the β-oxidation occurred in adipose tissue was recently confirmed in human preadipocytes [20]. This L-carnitine lipolytic action on adipose tissue could explain that, decreasing visceral fat accumulation, PLC treatment produced no changes in plasma levels of free fatty acids.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, in mature adipocytes, L-carnitine induced the expression of genes involved in β-oxidation and lipolysis and suppression of genes involved in adipogenesis [19]. Finally, the direct effect of L-carnitine on the β-oxidation occurred in adipose tissue was recently confirmed in human preadipocytes [20]. This L-carnitine lipolytic action on adipose tissue could explain that, decreasing visceral fat accumulation, PLC treatment produced no changes in plasma levels of free fatty acids.…”
Section: Discussionmentioning
confidence: 91%
“…In the mouse 3T3‐L1 cell line, it was shown that l ‐carnitine stimulates lipolysis‐activity and increases the expression of genes involved in β‐oxidation 15 . In human adipocytes, a significantly augmented β‐oxidation was demonstrated in cultured human primary preadipocytes as well as differentiated adipocytes after incubation with l ‐carnitine, compared to control cells 16 …”
Section: Discussionmentioning
confidence: 99%
“…Folium Nelumbinis, dried leaves of Nelumbo nucifera Gaertn, possesses various pharmacological activities, such as antioxidant (Lin, Kuo, Lin, & Chiang, ) and immunomodulatory (Liu et al, ), and has been extensively applied as a traditional Chinese medicine, tea and food supplements (Du et al, ; Mukherjee, Mukherjee, Maji, Rai, & Heinrich, ). Recent pharmacological studies demonstrated that Folium Nelumbinis also had an anti‐obesity effect by inhibiting the absorption of lipids and carbohydrates, accelerating lipid metabolism, and reducing triglyceride accumulation in adipocytes (Ahn et al, ; Du et al, ; Siegner et al, ). Thus, Folium Nelumbinis is used as a health food or as a Chinese traditional medicine (TCM) in elderly populations with hyperlipemia for the regulation of glucose and lipid metabolism, and the lipid‐lowering effect is supposed to be attributed to nuciferine (NF, Figure ).…”
Section: Introductionmentioning
confidence: 99%